Pengaruh Serat Polypropylene Terhadap Pola Retak dan Kuat Tekan Beton Berbasis Agregat Ringan Batu Apung - I.G.A. Neny Purnawirati; Fajar Surya Herlambang (Universitas Batanghari Jambi, 2026)
Lightweight concrete based on pumice aggregate has relatively high compressive strength; however, it is brittle and prone to cracking under loading, which can reduce the durability and service life of structures. The addition of polypropylene fibers is expected to improve crack resistance and enhance the mechanical properties of concrete. This study aims to evaluate the effect of polypropylene fiber addition on the compressive strength, splitting tensile strength, and crack pattern of structural lightweight concrete. An experimental method was employed using polypropylene fiber contents of 0%, 0.02%, 0.04%, and 0.06% by concrete volume. Tests were conducted on compressive strength, splitting tensile strength, and crack patterns at the age of 28 days. The results indicate that the addition of 0.02% polypropylene fibers produced the highest compressive strength of 22.20 MPa and the highest splitting tensile strength of 2.56 MPa compared to concrete without fibers. The addition of polypropylene fibers was also able to reduce crack width and control crack propagation, resulting in a more ductile failure behavior. However, higher fiber contents reduced the workability of the concrete mixture and decreased compressive strength due to less uniform fiber distribution. Based on these findings, the use of 0.02% polypropylene fiber is recommended as the optimum content to improve the mechanical performance and crack resistance of structural lightweight concrete without significantly reducing workability. Further studies are recommended to investigate fiber combinations or variations in concrete strength in order to evaluate long-term durability and crack behavior.